Factores que intervienen en la influencia de una lengua a otra. El euskera en un grupo de hablantes de Valdecarros - Urzelai Vicente, Ainhoa (Huarte de San Juan. Filología y Didáctica de la Lengua, 2018)
The aim of this work is to analyze the different factors that intervene in the influence of Basque on the Spanish of Valdecarros. On the one hand, the speech of eight valdecarrenians (with different age and linguistic profile) has been analyzed. On the other hand, their oral production and their linguistic attitude towards Basque and Basque speakers has been compared (information that has been obtained by surveys and interviews). The study has demonstrated that the amount of use of Basque is connected with the linguistic attitude that speakers have towards that language. It is true that Basque has not an important influence on the language of valdecarrenians, but, even so, among young people we have seen that few of them that keep in contact very often with Basques have adopted some traits from Basque and they use them when interacting with Basques. This linguistic accommodation seem to be totally conscious and it is influenced by the degree of affectivity towards the Basque community and the contact with the same.
Keywords: Language attitude; linguistic accommodation; influence of Basque on Spanish; degree of use of Basque; knowledge of Basque